Biodegradation of H acid by Bacillus subtilis and RP-HPLC method development for percent degradation estimation - Khan, R.R.M. (Maik Nauka Publishing / Springer SBM, 2016)
The industrial synthesis of pigments and dyes generates hazardous chemicals. These chemicals are released into water, soil and environment and regarded as a major source of environmental pollution. H acid is also an important dye intermediate. In this study, the focus was on the bacterial degradation of H acid (1-amino-8-naphthol-3,6-disulfonic acid) of different concentrations and its degradation estimation method. The biodegradation was identified by the help of IR, UV-Visible spectrophotometer and high performance liquid chromatography (HPLC). A method was developed for the estimation of percent biodegradation of H acid with the help of HPLC. The developed method was applicable on standard as well as biodegraded products and on other compounds with the sulfonic acid group. It was found that H acid of concentration 300 ppm and below can be completely degraded with Bacillus subtilis. However, over 300 ppm, the bacterial degradation did not work efficiently. Â© 2016, Pleiades Publishing, Ltd.